Single cell transcriptomics of cerebrospinal fluid cells from patients with recent-onset narcolepsy - Huth, Alina; Ayoub, Ikram; Barateau, Lucie; Gerdes, Lisa Ann; Severac, Dany; Krebs, Stefan; Blum, Helmut; Tumani, Hayrettin; Haas, Jürgen; Wildemann, Brigitte; Kümpfel, Tania; Beltrán, Eduardo; et al. (Journal of autoimmunity, 2024)
Narcolepsy is a rare cause of hypersomnolence and may be associated or not with cataplexy, i.e. sudden muscle weakness. These forms are designated narcolepsy-type 1 (NT1) and -type 2 (NT2), respectively. Notable characteristics of narcolepsy are that most patients carry the HLA-DQB1*06:02 allele and NT1-patients have strongly decreased levels of hypocretin-1 (synonym orexin-A) in the cerebrospinal fluid (CSF). The pathogenesis of narcolepsy is still not completely understood but the strong HLA-bias and increased frequencies of CD4+ T cells reactive to hypocretin in the peripheral blood suggest autoimmune processes in the hypothalamus. Here we analyzed the transcriptomes of CSF-cells from twelve NT1 and two NT2 patients by single cell RNAseq (scRNAseq). As controls, we used CSF cells from patients with multiple sclerosis, radiologically isolated syndrome, and idiopathic intracranial hypertension. From 27,255 CSF cells, we identified 20 clusters of different cell types and found significant differences in three CD4+ T cell and one monocyte clusters between narcolepsy and multiple sclerosis patients. Over 1000 genes were differentially regulated between patients with NT1 and other diseases. Surprisingly, the most strongly upregulated genes in narcolepsy patients as compared to controls were coding for the genome-encoded MTRNR2L12 and MTRNR2L8 peptides, which are homologous to the mitochondria-encoded HUMANIN peptide that is known playing a role in other neurological diseases including Alzheimer's disease.